Investigation on fatigue life behaviour of sustainable bio-based fibre metal laminate / D. Sivakumar...[et al.] - D., Sivakumar; L.F., Ng; Selamat, Mohd Zulkefli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Fibre-Metal Laminate (FML) is a hybrid structure which offers various advantages over conventional material. It had been used in automotive and aircraft sector since many years ago due to its lightweight and low cost properties. Previous study had shown FML had excellent fatigue crack resistance characteristic compared to metallic alloy. This study shows the effects of different composition of oil palm empty fruit bunch (OPEFB) fibre on the fatigue life behaviour, hardness properties and mass of FML. FML was manufactured based on randomly oriented short OPEFB fibre and annealed aluminium alloy 6061. The FML panels were formed by bonding aluminium layers to composite by using the hot press compression moulding method with picture frame mould. Static test was conducted prior to fatigue test at quasi-static manner. The fatigue life of monolithic aluminium was investigated and set as a benchmark. The fatigue test was conducted at load levels of 80 to 95% of ultimate tensile strength using Universal Testing Machine. Results suggest that FML with 30% fibre loading had the highest fatigue resistance compared to other fibre composition. The mass of FML had been identified less than aluminium up to 30%. The hardness strength increases with increase fibre composition for composite while the hardness strength is relatively constant for FML.